The evolution of the actin binding NET superfamily - Hawkins, Timothy J.; Deeks, Michael J.; Wang, Pengwei; Hussey, Patrick J. (Frontiers in Plant Science, 2014)
The arabidopsis Networked protein superfamily are plant-specific actin binding proteins which specifically label different membrane compartments and identify specialized sites of interaction between actin and membranes unique to plants. There are 13 members of the superfamily in arabidopsis which group into 4 distinct clades or subfamilies. NET homologues are absent from the genomes of metazoa and fungi, furthermore in Plantae NET sequences are also absent from the genome of mosses and more ancient extant plant clades. A single subfamily of the NET proteins are found encoded in the club moss genome; an extant species of the earliest vascular plants. Gymnosperms have examples from subfamilies 4 and 3 with a hybrid form of NET1 and 2 which shows characteristics of both NET1 and NET2. In addition to NET3 and 4 subfamilies, the NET1 and pollen-expressed NET2 subfamilies are only found as independent sequences in angiosperms. This is consistent with the divergence of reproductive actin. The four subfamilies are conserved across monocots and eudicots with the numbers of members of each clade expanding at this point due in part to regions of genome duplication. Since the emergence of the NET superfamily at the dawn of vascular plants they have continued to develop and diversify in a manner which has mirrored the divergence and complexity of plant species through evolution in the ‘March of Progress’.